2019
DOI: 10.1002/pat.4597
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and properties of 1,2‐polybutadiene grafting with poly(1,3‐butadiene)‐block‐(dimethylsiloxane)

Abstract: The development of silica‐filling elastomers with high mechanical performance and good processability is still a great challenge. In this study, we fabricated siloxane‐grafted atactic 1,2‐polybutadiene (1,2‐PB) rubber through grafting poly(1,3‐butadiene)‐block‐(dimethylsiloxane) (PB‐b‐PDMS) onto 1,2‐PB molecular chains by coordination polymerization using a molybdenum (Mo)‐based catalyst system. The PB‐b‐PDMS with active double bonds was synthesized by anionic polymerization. Fourier transform infrared analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…A polybutadiene rubber, for application as a silica-filled elastomer, was produced by grafting a block copolymer of butadiene and dimethylsiloxane on polybutadiene [ 7 ]. The block copolymer was produced by sequential anionic polymerisation of butadiene and octamethyltetrasiloxane.…”
Section: Graft Copolymers Bearing Polysiloxane Unitsmentioning
confidence: 99%
See 1 more Smart Citation
“…A polybutadiene rubber, for application as a silica-filled elastomer, was produced by grafting a block copolymer of butadiene and dimethylsiloxane on polybutadiene [ 7 ]. The block copolymer was produced by sequential anionic polymerisation of butadiene and octamethyltetrasiloxane.…”
Section: Graft Copolymers Bearing Polysiloxane Unitsmentioning
confidence: 99%
“…The Si-O bond is a highly versatile chemical linkage that can be found in a great variety of materials and molecules, linking together inorganic [ 1 , 2 , 3 ] and organic species [ 4 , 5 , 6 ], as well as being a building block for polymers [ 7 , 8 , 9 ] and sophisticated 3D oligomers [ 10 , 11 ]. In the role of linkage, the siloxane bond is robust, chemically resistant to an array of environments and easily established, e.g., via the reaction of silanes with organic or inorganic hydroxyl groups [ 6 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Polyamide 6,12 (PA6,12) is a well‐known engineering thermoplastic, which has been widely used in automotive, electrical, and medical application 1–3 . The PA6,12 has a typical structure of amide group and methylene chain in the main chain 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Small molecules can also toughen polyamide due to plasticizing effect 16 . For instance, it has been reported that polyethylene glycol substantially improves PA6 toughness due to plasticizing effect 1 . Cai et al 16 synthesized a small molecule chain extender to modify PA6 performance, and its impact strength was ~1.7 times higher than that of the neat PA6 matrix.…”
Section: Introductionmentioning
confidence: 99%